From Novice to Expert: A Surgical Care Practitioner's Reflection on Their Role Development. Issue 10 (October 2016) - Quick, J
As co-lead for the AfPP Advancing Surgical Roles Specialist Interest Group, I was recently asked about which procedures a surgical care practitioner (SCP) can be trained to undertake and how the SCP role can be developed fully within the remit of the surgical team. This question enabled me to reflect upon and explore the development of my own role of a vascular and general SCP using Benner's adaptation of the Dreyfus' expertise acquisition model that describes the transition that nurses and, one could argue, all healthcare professionals make from novice to expert practitioners (Benner 1984) (Figure 1)